2015
DOI: 10.5815/ijmecs.2015.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Web-enabled Simulated and Remote Control Virtual Laboratory of Transducer

Abstract: Abstract-In the era of Information and Communication Technology (ICT), virtual laboratories in the field of engineering and sciences have gained popularity, as a smart way of imparting practical and theoretical education. This paper discusses the realization of webenabled simulated and remote control virtual laboratory of transducer based on one of the modular transducer kit/trainer commonly used in conducting experiments in Instrumentation and Control Engineering curriculum or related fields. Using component-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It is worth indicating that, despite high potential of modern ICT, complex e-learning tools are of limited use in the process of study of academic disciplines, due to the lack of certified virtual tools. In the era of Information and Communication Technology (ICT), virtual laboratories in the field of engineering and sciences have gained popularity, as a smart way of imparting practical and theoretical education [10].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth indicating that, despite high potential of modern ICT, complex e-learning tools are of limited use in the process of study of academic disciplines, due to the lack of certified virtual tools. In the era of Information and Communication Technology (ICT), virtual laboratories in the field of engineering and sciences have gained popularity, as a smart way of imparting practical and theoretical education [10].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the virtual laboratory developed provided access opportunities for real users without any time limitations, as well as real-time monitoring capabilities, and hence achieved pedagogically favorable results. 10 Another recent study introduces a new web-based virtual laboratory called SHRIMP VL to help teach the Precision High Resolution Ion Micro Probe (SHRIMP) application. This virtual laboratory is specifically designed to help learn the operational process procedure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the teaching of students in technical specialties are increasingly used software products for synthesis, simulating and testing of analog, digital and analogdigital circuits, etc. [1]; [2]; [10]; [11]; [12]; [13]; [14]; [15]; [16]. Computer modeling and simulations of logic circuits through the software product CircuitMaker can be used in the lectures and in the laboratory exercises on the course "Analysis and synthesis of logic circuits".…”
Section: Application Of the Software Product Circuitmaker In Thementioning
confidence: 99%